MnFe-layered double hydroxides grown on spherical SiO2 to construct core-shell heterostructures for enhanced simultaneous photocatalytic redox Reactions of Cr(VI) and As(III). (December 2022) - Mohapatra, Lagnamayee; Tsang, Yiu Fai; Dou, Xiaomin; Baek, Kitae
Abstract: Synergic oxidation and reduction of As(III) and Cr(VI) offer unique advantages for wastewater treatment. Herein, we report the fabrication of MnFe layered double hydroxide (LDH) nanoplatelets arranged on the surface of a SiO2 nanosphere to form a novel visible-active LDH@SiO2 core-shell photocatalyst. The activity of the samples was evaluated by observing the simultaneous oxidation of As(III) and reduction of Cr(VI) under visible light irradiation. The remarkably enhanced photocatalytic activity of LDH@SiO2 can be elucidated in terms of efficient charge carrier generation, transport, and separation owing to the well-contacted core/shell interface, high surface area, mesoporous surface, and surface hydrophilicity. The composites exhibited considerably high activities for oxidation of As(III) and reduction of Cr(VI) when they coexisted, which were approximately 2 and 2.2 times higher than the presence of As(III) or Cr(VI) along. The photocatalytic mechanism was investigated using radical scavenger studies. The result supported that the redox reactions can be performed simultaneously via a synergistic oxidation-reduction mechanism in the presence of LDH@SiO2 core-shell photocatalyst under visible light irradiation. This work provides new paths for simultaneous mitigation of As(III) and Cr(IV) contamination by employing LDH-based photocatalyst and proves its bright potential to treat wastewater. Graphical abstract: Synergistic effect of Cr(VI) reduction and As (III) oxidation over LDH@SiO2 photocatalyst under visible light irradiation. Unlabelled Image Highlights: LDH@SiO2 core-shell catalysts were successfully synthesized for simultaneous As(III)/Cr(VI) photo-redox reactions. The core-shell structure enhanced photocatalytic activity due to efficient charge separation. Photogenerated holes and hydroxyl radicals play a crucial role in As(III) oxidation and electrons for Cr(VI) reduction. Synergistic redox reactions of As(III) and Cr(VI) were achieved.